Trans-Perineal Template-Guided Mapping Biopsy vs. Freehand Trans-Perineal Biopsy in Chinese Patients With PSA < 20 ng/ml: Similar Cancer Detection Rate but Different Lesion Detection Rate - He, Bi-Ming; Chen, Rui; Shi, Zhen-Kai; Xiao, Guang-An; Li, Hu-Sheng; Lin, Heng-Zhi; Ji, Jin; Peng, Hong-Xiang; Wang, Yan; Sun, Ying-Hao; Wang, Hai-Feng (Frontiers in Oncology, 2019)
The present study aimed to investigate the diagnostic efficacy and the regional location of prostate cancer (PCa) as well as the accuracy of assessment between trans-perineal template-guided mapping biopsy (TTMB) and freehand trans-perineal biopsy (FTPB) for men with PSA<20ng/ml. Thus, we evaluated 623 consecutive patients with PSA<20ng/ml who had prostate biopsies in our institute between July 2017 and September 2018. Patients were divided into two groups based on different biopsy methods: 217 (34.83%) patients with TTMB and 406 (65.17%) with FTPB. 36 patients with TTMB and 80 with FTPB had continued undergone radical prostatectomy after a cancer diagnosis. Then the Gleason score of the biopsy and the post-radical prostatectomy specimens in each patient were compared. Overall, the PCa detection rate was 34.35%. There was no significant difference in PCa detection rate between TTMB and FTPB (35.48% vs. 33.74%, respectively; p=0.663). Besides, the detection rate of significant PCa (Gleason score≥7) in TTMB was 29.03% while FTPB was 23.89% (p=0.162). The detection rate at the apex of the prostate was higher than the detection rate at the base of the prostate (9.80% vs. 5.79%; p<0.01) when performing the TTMB. The FTPB would miss 10% of the positive diagnosis and almost half of the lesions. The upgraded of Gleason score from biopsy to post-radical prostatectomy was 16.67% with the TTMB and 36.25% with the FTPB (p=0.034). The TTMB had a similar cancer detection rate, but a higher lesion detection rate and more accuracy in assess the actual Gleason score when comparing to FTPB for men with PSA<20ng/ml. By performing a 20-core TTMB, the cancer detection rate at the apex of the prostate was higher than the base.